The past and the present in decision-making: the use of conspecific and heterospecific cues in nest site selection - Sami M. Kivelä; Janne-Tuomas Seppänen; Otso Ovaskainen; Blandine Doligez; Lars Gustafsson; Mikko Mönkkönen; Jukka T. Forsman (My University, 2025)
Nest-site selection significantly affects fitness, so adaptations for assessment of the qualities of available sites are expected. The assessment may be based on personal or social information, social information referring to the observed location and performance of both con- and heterospecific individuals. Contrary to large-scale breeding habitat selection, small-scale nest-site selection within habitat patches is insufficiently understood. We analyzed nest-site selection in the migratory collared flycatcher Ficedula albicollis in relation to present and past cues provided by conspecifics and by resident tits within habitat patches by using long-term data. Collared flycatchers preferred nest boxes that were occupied by conspecifics in the previous year. This preference was strongest in breeding pairs where both individuals bred in the same forest patch in the previous year. The results also suggest preference for nest boxes close to boxes where conspecifics had a high breeding success in the previous year, and for nest boxes which are presently surrounded by a high number of breeding great tits Parus major. The results indicate social information use in nest-site selection at a small spatial scale, where collared flycatchers use conspecific cues with a time lag of one year and heterospecific cues instantly.